‘Why have STI rates increased in the middle age population?’ -A critical review - Monsell, Ellen (2013)
Background- Recent reports have shown that individuals aged 45-64 are at an increased risk of contracting a sexually transmitted infection, with rates rising steadily over the last several years. Sexual health research has historically focused on the needs and behaviours of the young, with more recent interest into the needs of the older population. This has led to an interest into the literature available regarding the population in the middle of these two groups; the ‘middle age’ population. Method- A critical review was conducted using selected keywords generated from a mind mapping exercise. These search terms were applied to electronic literature databases, focused on a range of health and social care literature to identify appropriate studies that focused on STI rates in the middle age population. Inclusion and exclusion criteria where provisionally applied to ensure appropriate literature was identified and 15 articles were included in the review overall. Findings- Four key themes were identified in the literature relating to STI risk of middle age individuals. These were; deficient and variable condom use and knowledge, multiple sexual partners of males and associated risk behaviours, divorce, separation and new relationships and physiological factors associated with STI risk, including erectile dysfunction medication and asymptomatic infections. A lack of definition of the middle age population as well as an underrepresentation of women was highlighted within this evidence base. Recommendations- This review highlights the need for more substantial definitions of the middle age group within sexual health literature to ensure the health needs of this age group are understood. Further consideration of female behaviour traits in association with STI risk alongside further research into the themes highlighted by this critical review, focused iv specifically on the middle age group would be beneficial for the development of the evidence base associated with this subject.